COMPETENCY-BASED APPROACH AND ISSUES OF SELF-EDUCATION IN MODERN EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the theoretical and methodological foundations of the competency-based approach in the modern education system and the issues of forming self-education competence. In particular, it covers pedagogical mechanisms for directing the educational process to results, developing independent thinking, reflection, self-assessment and self-management skills in students. The article presents scientific conclusions on effective methods and prospects for developing self-education competence.